Deficiencies in Man, Money, Method, Material, and Machine Contribute to the Non-Implementation of Medical Record Retention and Destruction - Sheyla, Lusitha Prayuni; Muflihatin, Indah; Erawantini, Feby; Swari, Selvia Juwita; Alfiansyah, Gamasiano (Jurnal Penelitian Kesehatan SUARA FORIKES, 2026)
Medical record retention and destruction are essential components of health information management to ensure data security, maintain service efficiency, and comply with regulatory standards. Failure to implement these processes properly can lead to the accumulation of inactive records, increased risk of data breaches, and inefficiencies in storage management within healthcare facilities. This study aimed to identify the factors contributing to the non-implementation of medical record retention and destruction using the five management elements (man, money, method, material, and machine). This study employed a qualitative research design. The research subjects consisted of one head of medical records, one registration officer, and one filing officer. Data were collected through observation, interviews, and documentation. The findings revealed that from the man factor, the causes included insufficient knowledge regarding medical record destruction, educational backgrounds of staff (two high school graduates and one vocational nursing graduate), and lack of participation in relevant training. From the method factor, there was no standard operating procedure (SOP) for medical record destruction. From the money factor, no budget had been allocated for the implementation of medical record destruction. From the machine factor, there was no equipment available to carry out the destruction process. From the material factor, there was a lack of storage racks for medical record files. In conclusion, the non-implementation of medical record retention and destruction is influenced by deficiencies across all five management elements (man, money, method, material, and machine).Keywords: medical record destruction; community health care; man; money; method; material; machine